The ability of GexGa4S96-x chalcogenide glasses dissolving rare earth probed by x-ray photoelectron spectra analysis. (12th June 2019) - Xu, Qin; Yang, Xinyu; Zhang, Mingjie; Wang, Rongping
Abstract: We have synthesized the ternary chalcogenide glasses Gex Ga4 S96-x (x = 22.5, 27, 30, 33, 36), and studied the structural evolution of the glasses by the high-resolution x-ray photoelectron spectra (XPS) technique. We decomposed S 2p, Ge 3d and Ga 3d core XPS spectra into different structural units and found that, with increasing Ge content, part of S-Ge(Ga)-S structure changes into (Ge, Ga)-Ge(Ga)-S, and finally Ge(Ga) clusters appear in the chemically stoichiometric and S-poor glasses. The formation of Ge(Ga) clusters in the chemically stoichiometric and S-poor glasses indicates that, only S-rich Ge–Ga–S glasses can be effectively used as hosts for the doping of rare earth ions, in which no Ga clusters exist and the rare earth ions can be uniformly distributed in the glasses to avoid any possible photoluminescence quenching.